A descoberta das correntes neutras das interações fracas - Fortes, E.C.F.S. [UNESP]; Tijero, M.C.; Pleitez, V. [UNESP] (Sociedade Brasileira de Física, 2007)
Neste artigo fazemos uma crônica sobre a descoberta das correntes neutras fracas por dois grupos experimentais independentes. Consideramos também um pouco da história das correntes neutras para contextualizar melhor essa descoberta que foi decisiva para a posterior confirmação do modelo padrão eletrofraco. Esta descoberta deixa clara a dificuldade de considerar os resultados experimentais como sendo completamente independentes da teoria.

In this paper we narrate the discovery of the weak neutral currents by two independent experimental collaborations. We also give a brief review of the history of the neutral currents in order to give a clear description of the context of that discovery which was decisive for a later confirmation of the electroweak standard model. This discovery shows the difficulty for considering the experimental results as being completely independent of the theory.
The discovery of the weak interactions's neutral currents
Keywords: correntes neutras; bósons Z; modelo eletrofraco; neutral currents; Z boson; electroweak model